Christian-Muslim Relations. A Bibliographical History Volume 17. Britain, the Netherlands and Scandinavia (1800-1914) - Thomas, David,; Chesworth, John A., (The History of Christian-Muslim Relations ;, 2021)
Christian-Muslim Relations, a Bibliographical History Volume 17 (CMR 17) covering Great Britain, the Netherlands and Scandinavia in the period 1800-1914, is a further volume in a general history of relations between the two faiths from the 7th century to the early 20th century. It comprises a series of introductory essays and the main body of detailed entries. These treat all the works, surviving or lost, that have been recorded. They provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 17, along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section Editors: Clinton Bennett, Luis F. Bernabé Pons, Jaco Beyers, Emanuele Colombo, Lejla Demiri, Martha Frederiks, David D. Grafton, Stanisław Grodź, Alan Guenther, Vincenzo Lavenia, Arely Medina, Alain Messaoudi, Gordon Nickel, Claire Norton, Radu Păun, Reza Pourjavady, Douglas Pratt, Charles Ramsey, Peter Riddell, Umar Ryad, Cornelia Soldat, Karel Steenbrink, Charles Tieszen, Carsten Walbiner, Catherina Wenzel.